A Prospective Study Comparing Continuous Versus Interrupted Suture Techniques in Midline Abdominal Wound Closure - Bharti, Shiv Vansh; Sharma, Anup (Journal of Nepalgunj Medical College, 2020)
Introduction: Wound closure after midline laparotomy is an essential part of surgery to produce a healthy and a strong scar. There is an alternative interrupted method of closure as compared to conventional continuous method of closure. Many comparative studies have shown different outcomes. So, we wanted to evaluate the outcome of different techniques in our setting.Aims: To compare the outcome of Interrupted abdominal closure and continuous abdominal closure in midline laparotomy wound.Methods: This was a prospective comparative study conducted in the Department of Surgery of Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke, Nepal for a duration of 1 year. A total of 60 patients were selected randomly to receive either continuous or interrupted abdominal closure in midline laparotomy wound. Wound was evaluated in terms of wound discharge, infection and wound dehiscence.Results: The mean age of the patients was 38.38 years. Most commonly, the patients presented with duodenal ulcer perforation with peritonitis. The average time taken for abdomen closure in group A (16.77 minutes) was significantly less as compared to group B (27.77 minutes). The average cost of sutures for group B (Rs 1322.97) was higher than that of sutures for group A (Rs 1118) with p value of